Computer printed denture labeling: A simplified technique - Adhikari, A; Mathema, SRB; Maksey, B; Maharjan, SK; Dhyako, N; Gurung, A; Pandey, B; Subedi, S (Journal of Nepalese Prosthodontic Society, 2021)
Importance and benefits of denture labeling have been widely described in forensic and dental community. It helps in identification and prevents the probability of losing dentures in geriatric edentulous patient. Several methods have been described in literature for the purpose of labeling denture. The article fully describes an inclusive method which is simple, economical, permanent and is done with equipment readily available in a laboratory.